2019
DOI: 10.1186/s12913-019-4795-5
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 diabetes and healthcare resource utilisation in the Kingdom of Bahrain

Abstract: BackgroundType 2 diabetes is a growing health challenge in the Kingdom of Bahrain, and the disease exerts significant pressure on the healthcare system. The aim of this study was to assess the annual costs and understand the drivers of those costs in the country.MethodsA sample of 628 patients diagnosed with type 2 diabetes were randomly selected from primary healthcare diabetes clinics, and the direct medical and indirect costs due to type 2 diabetes were analysed for a one-year period. The study used patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 30 publications
0
15
1
3
Order By: Relevance
“…A cross sectional study reported that type 2 diabetes exerts a significant pressure on Bahrain's healthcare system—primarily due to costly diabetes-related complications. Thereby, reducing the risk factors for diabetes is mandatory to minimize disabling and expensive complications ( 33 ). Additionally, multivariate analysis for a wide community-based survey in Pakistan using glycated hemoglobin revealed a significant link between type 2 diabetes and old age.…”
Section: Resultsmentioning
confidence: 99%
“…A cross sectional study reported that type 2 diabetes exerts a significant pressure on Bahrain's healthcare system—primarily due to costly diabetes-related complications. Thereby, reducing the risk factors for diabetes is mandatory to minimize disabling and expensive complications ( 33 ). Additionally, multivariate analysis for a wide community-based survey in Pakistan using glycated hemoglobin revealed a significant link between type 2 diabetes and old age.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, we replaced our estimates of the impact of stroke and type 2 diabetes mellitus on absenteeism and presenteeism with estimates used in a recent unpublished Kuwait study [19]. These estimates were derived from four previously published studies: Salman, Alsayyad, and Ludwig [3], Mitchell and Bates (2011) [20], Wang, Beck, and Berglund et al (2003) [21], and Bommer, Heesemann, and Sagalova et al [22].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To date, most of the few studies that have been conducted focused on one condition in one country. Salman, AlSayyad, and Ludwig (2019), for example, estimated the direct cost of type 2 diabetes mellitus in Bahrain [3]. Al-Busaidi, Habibullah, and Soriano (2013) estimated the direct cost of asthma in Oman [4].…”
Section: Introductionmentioning
confidence: 99%
“…In terms of economic impact, T2D places enormous pressure on GCC health budgets. For instance, Qatar, UAE, and Bahrain have spent, respectively, $0.5bn, $2bn, and $0.27bn directly on T2D diabetes in 2015 [ 30 , 31 ]. Likewise, in KSA, 34% ($10bn) of the 2014 health budget ($29 billion) was allocated to diabetes treatment.…”
Section: Diabetes In the Gcc: The Top Health Prioritymentioning
confidence: 99%
“…Unfortunately, economic studies that estimate the real impact of diabetes on economic productivity in GCC are very scarce. For example, a recent study from Bahrain [ 30 ] estimated at $3.62 million the cost due to diabetes-associated absenteeism in 2015, when the number of subjects with diabetes was 154300 (IDF Atlas, 2015). With 202700 subjects with diabetes today (IDF, February 2020), this estimation has likely increased.…”
Section: Diabetes In the Gcc: The Top Health Prioritymentioning
confidence: 99%